(untitled) (Al-Farooq Journal of Sciences, 2026)
This article analyzes the transformation of Turkish-Israeli relations from a strategic partnership in the 1990s to a hostile and antagonistic relationship in the 2000s through the lens of the Copenhagen School’s securitization theory. While Turkey was the first Muslim-majority state to recognize Israel in 1949, bilateral relations reached their peak during the 1990s with extensive cooperation in military, economic, and cultural fields, before deteriorating sharply following the collapse of the peace process, the Gaza War (2008-2009), and the Mavi Marmara flotilla incident (2010). The study seeks to answer a central question: Why has the unparalleled positive nature of relations in the 1990s been replaced by a toxic environment in the 2000s? To address this, the paper employs a dual theoretical framework. First, it uses Realist theory and the military sector of security to explain the 1990s rapprochement. During the Cold War and its immediate aftermath, the Turkish military-bureaucratic elite, as the primary securitizing actor, framed threats such as the PKK, Syria, Iran, and political Islam as existential threats to the secular Kemalist state — the main referent object. This securitization legitimized an extraordinary alignment with Israel as the only democratic, secular, and Western-oriented partner in the region, providing access to military technology and strategic balancing. Second, the paper applies societal security and Constructivist theory to explain the post-2000s rupture. With the rise of the AKP, the decline of military tutelage in foreign policy-making, and the adoption of the "zero problems with neighbours" policy, the referent object shifted from state sovereignty to collective identity and societal security. The conservative constituency re-securitized Israeli policies toward Palestine as an existential threat to Islamic and humanitarian identity, moving the issue from normal politics to emergency politics and justifying extraordinary diplomatic measures, including the downgrading of relations. The findings demonstrate that Copenhagen School securitization theory not only explains the divergent security perceptions in the two periods but also reveals the shifting civil-military dynamics in Turkish foreign policy making.